Pelatihan Modifikasi Motif Khas Sulawesi Melalui Aplikasi Ibis Paint pada UMKM Kota Makassar untuk Mendorong Pertumbuhan Ekonomi Kreatif di Era Digitalisasi - Andi Nuralfiah; Luthfiani Jusuf; Perawati Simaremare; Nur Widya Anriyana; Muh. Fadhil Supriadi (Yayasan Insan Literasi Cendekia (INLIC) Indonesia, 2026)
The Micro, Small, and Medium Enterprises (UMKM) sector is experiencing shifts in production and marketing due to advances in digital technology. This includes creating products tailored to local culture. As a center of the creative industry in Eastern Indonesia, Makassar has great potential to develop distinctive South Sulawesi styles, including the Bugis-Makassar style (Lipa Sabbe and geometric), the Toraja style, and other variations of traditional styles. The aim of this service is to provide UMKM practitioners in Makassar City with the ability to transform authentic Sulawesi colors using the Ibis Paint digital design application. This will support the growth of the creative economy in the digital era. The activity commenced in January 2026 and involved 60 UMKM participants with a participatory training approach, including socialization, demonstrations, design practice, mentoring, and evaluation of the works. The results of the activities show that participants are able to use the basic to advanced features of the Ibis Paint application to create digital motif designs that are more creative, flexible, and have commercial value. Therefore, this training will enhance the capabilities of creative UMKM and strengthen the culture-based creative economy ecosystem in Makassar City.